Effective combination of aligned nanocomposite nanofibers and human unrestricted somatic stem cells for bone tissue engineering - Bakhshandeh Behnaz; Soleimani Masoud; Ghaemi Nasser; Shabani Iman (Acta Pharmacologica Sinica; Vol 32, No 5 (May 2011): Acta Pharmacologica Sinica, 2016)
Aim: Bioartificial bone tissue engineering is an increasingly popular technique to solve bone defect challenges. This study aimed to investigate the interactions between matrix composition and appropriate cell type, focusing on hydroxyapatite (HA), to achieve a more effective combination for bone regeneration. Methods: Human unrestricted somatic stem cells (USSCs) were isolated from placental cord blood. The cellular and molecular events during the osteo-induction of USSCs were evaluated for 21 d under the following conditions: (1) in basal culture, (2) supplemented with hydroxyapatite nanoparticle (nHA) suspension, and (3) seeded on electrospun aligned nanofibrous poly-ε-caprolactone/poly-L-lactic acid/nHA (PCL/PLLA/nHA) scaffolds. The scaffolds were characterized using scanning electron microscope (SEM), fourier transform infrared spectroscopy (FTIR) and tensile test. Results: Maintenance of USSCs for 21 d in basal or osteogenic culture resulted in significant increase in osteoblast differentiation. With nHA suspension, even soluble osteo-inductive additives were ineffective, probably due to induced apoptosis of the cells. In contrast to the hindrance of proliferation by nHA suspension, the scaffolds improved cell growth. The scaffolds mimic the nanostructure of natural bone matrix with the combination of PLLA/PCL (organic phase) and HA (inorganic phase) offering a favorable surface topography, which was demonstrated to possess suitable properties for supporting USSCs. Quantitative measurement of osteogenic markers, enzymatic activity and mineralization indicated that the scaffolds did not disturb, but enhanced the osteogenic potential of USSCs. Moreover, the alignment of the fibers led to cell orientation during cell growth. Conclusion: The results demonstrated the synergism of PCL/PLLA/nHA nanofibrous scaffolds and USSCs in the augmentation of osteogenic differentiation. Thus, nHA grafted into PCL/PLLA scaffolds can be a suitable choice for bone tissue regeneration.